Enhancing the emergency department experience for older adults: Study protocol for the implementation of a comfort menu and cart - Silvia A. Ferreira; Fernanda Bellolio; Susan M. Bower; Luis Fernando Penna; Magali A. L. Marion; Marlon R. Aliberti; Thiago J. Avelino-Silva; Christian V. Morinaga; Pedro Kallas Curiati (PLoS ONE, 2025)
Introduction The aging of the population is a global phenomenon, with projections indicating a significant increase in the proportion of individuals aged 65 years and older by 2050. This demographic shift requires adapting emergency department (ED) services to meet the specific demands of older patients, who often present with multiple comorbidities and face challenges such as sensory and cognitive difficulties. EDs, traditionally designed for acute illness and injury management, may not be adequately equipped to meet the unique needs of this vulnerable population. This can result in suboptimal patient experiences, prolonged ED stays, increased hospitalizations, and poorer outcomes. Methods This study protocol outlines a before-and-after study to evaluate the impact of implementing a comfort menu and cart on the experience and outcomes of older patients treated in the ED. The study will be conducted in the ED of Hospital Sírio-Libanês (HSL), a tertiary private hospital in São Paulo, Brazil. Patients aged 65 and older who presented to the ED will be eligible for inclusion. Participants will be recruited in two phases: pre-intervention and post-implementation of the comfort menu and cart. Data will be collected through patient and staff interviews, chart reviews, and a 30-day follow-up interview. Patient experience, staff experience, length of hospital stays, hospital costs, ED readmissions, falls, delirium incidence, quality of life, functional status, cognitive performance, and mortality will be assessed. Expected results We expect to demonstrate the positive impact of implementing the comfort menu and cart in the ED on patient-centered outcomes. We anticipate improvements in the experience of older patients and medical and multidisciplinary staff, and hope to identify improvements in other exploratory outcomes. Trial registration number ClinicalTrials.gov NCT06681376.